Adolescent well-being amid the COVID-19 pandemic: Are girls struggling more than boys? ... - Halldorsdottir, Thorhildur; Thorisdottir, Ingibjorg E.; Meyers, Caine C. A.; Asgeirsdottir, Bryndis Bjork; Kristjansson, Alfgeir L.; Valdimarsdottir, Heiddis; Allegrante, John P.; Sigfusdottir, Inga Dora (Columbia University, 2021)
Background: Differential effects of the coronavirus SARS-CoV-2 (COVID-19) pandemic and associated public restrictions on adolescent girls and boys are emerging but have not been elucidated. This study examined gender differences across broad indicators of adolescent well-being during the COVID-19 pandemic in Iceland, and explored potential explanations for these differences. Methods: In total, 523 youth (56.5% girls) born in Iceland in 2004 completed measures on mental health problems (depressive symptoms, anger and suicide attempts) and measures designed for this study to assess broad indicators of adolescent well-being (e.g., day-to-day life, academic performance, family and peer relationships, and mental and physical health) and behavioral changes during the COVID-19 pandemic. Mental health problems during the pandemic were compared to expected scores based on nationwide ratings of same-aged peers in 2018. Results: Although both boys and girls appeared affected, girls reported a greater negative impact ...